Analisis Potensi Kebangkrutan Pada Perusahaan Konstruksi yang Terdaftar di Bursa Efek Indonesia (BEI) untuk Periode 2019-2023 - Alfathan, Mohammad Farhan; Titisari, Kartika Hendra; Mursito, Bambang (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the potential for bankruptcy in construction companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023 by employing four bankruptcy prediction models: Altman Z-Score, Springate, Zmijewski, and Grover. The construction industry plays a vital role in national infrastructure development, yet it remains vulnerable to economic pressures, project financing challenges, and cash flow volatility, all of which may lead to financial instability. This research uses a quantitative approach with secondary data derived from annual financial statements of 16 construction companies collected over five years. Each model is applied to assess the level of bankruptcy risk, followed by the Kruskal-Wallis test to examine significant differences among the models, and further evaluated through accuracy and Type II error tests to determine each model’s reliability. The results indicate classification variations among the models in identifying companies within the Distress Zone. The Altman Z-Score model proves to be the most sensitive in detecting bankruptcy risk, while the Grover model demonstrates the highest accuracy rate at 93.75% and the lowest Type II error rate at 6.25%. Conversely, the Springate model records the lowest accuracy. The study concludes that companies with healthier capital structures and efficient financial management tend to remain more stable, whereas those burdened with high debt and low liquidity are more prone to financial distress.